A herbivore-induced plant volatile of the host plant acts as a collective foraging signal to the larvae of the meadow moth, Loxostege sticticalis (Lepidoptera: Pyralidae). (October 2019) - Wen, Ming; Li, Ertao; Chen, Qi; Kang, Hui; Zhang, Shuai; Li, Kebin; Wang, Yinliang; Jiao, Yin; Ren, Bingzhong
Graphical abstract: Highlights: Xenopus laevis oocyte voltage clamp results showed LstiOR5 is narrowly tuned to MeSA. L. sticticalis larvae preferred foraged leaves over un-foraged ones, MeSA played key role in this preference. Silencing on LstiOR5 significantly decreased EAG response and the preference to MeSA. Abstract: The meadow moth Loxostege sticticalis is a serious agricultural pest that feeds on the leaves of many economic crops, such as sugar beet, soybean, sunflower, and potato. In addition to the rapid migration of adult moths, the collective foraging behavior of the larvae is also thought to be involved in the search for new food sources and substantially contributes to the expansion of the infested area. However, whether and how the chemical signals take part in this process remains unknown. In this study, two larva-specific expressed odorants, LstiOR5 and LstiOR6, were successfully cloned and deophanized. A heterologous study on Xenopus laevis oocytes showed that several host plant volatiles could evoke LstiOR responses in a dose-dependent manner. One herbivore-induced plant volatile (HIPV) of soybean leaves, methyl salicylate (MeSA), exerted attractive effects on the L. sticticalis larvae at all tested concentrations. Further foraging choice assays showed that the L. sticticalis larvae preferred foraged soybean leaves over unforaged leaves. When MeSA was artificially added to unforaged leaves, the unforaged leaves were preferred over the foraged leaves. In addition, GC-MS analysis demonstrated that MeSA was induced by the foraging behavior of the larvae and acted as a collective food signal in L. sticticalis . Moreover, in situ hybridization showed that LstiOR5 was highly expressed in larval antenna neurons. When LstiOR5 was silenced, both the electrophysiological response of the antenna to MeSA and the preference for foraged leaves were significantly decreased, suggesting that LstiOR5 is involved in the collective foraging behavior of L. sticticalis . Our results clarified the chemical signals that trigger the collective foraging behavior of L. sticticalis and provided more evidence for the molecular mechanism underlying the expansions of their infested areas at a peripheral olfactory sensing level. These findings could facilitate the development of potential control strategies for controlling this pest and provide a potential gene target that correlates with the collective foraging behavior of L. sticticalis, which might lead to better pest management.